Numerical Analysis of Stress-Strain State of Vertical Cylindrical Oil Tanks with Dents - Buganova, S.N.; Avramov, K.V. (Проблеми машинобудування, 2018)
The destruction of vertical cylindrical tanks results in both human and economic losses. Despite constant improvement of the manufacturing technology of cylindrical tanks, a complete analysis of the influence of various dents on stress-strain states was not performed. Dents are the most dangerous, unpredictable zones that are studied a little. It should be specially emphasized that there is no system to assess the stress concentrations in the dent zone, and the regulatory documents for the construction and operation of oil tanks do not take into account the stress-strain state in the dent. The paper presents the results of a finite element analysis of the stress-strain states of the cylindrical tanks with spherical dents. On the basis of the finite element analysis, approximate relationships are derived for stress concentration coefficients that can be used to calculate various sized cylindrical tanks with different dents. A cylindrical tank with a spherical dent is investigated. The reasons for dent formation are not considered. It is assumed that there are no residual stresses in the dent area. Simulating the stress-strain state of the tank, the conclusion is made that the greatest stresses are observed in the lower part of the dent. As in the lower part of the dent, the internal pressure of fuel oil is greater. At high values of the relative depth of the dent the maximum stresses are observed only at the lower boundary of the dent. An approximation technique for calculating the stress concentration factor in the dent is proposed. An approximate model of the stress concentration factor due to the dent size parameters is built for an example tank Разрушение вертикальных цилиндрических резервуаров приводит к человеческим и экономическим потерям. Несмотря на постоянное усовершенствование технологии производства резервуаров подробного анализа влияния различных вмятин на их напряженно-деформируемое состояние не было сделано. Вмятины – наиболее опасные области констhукции, которые мало исследованы. Особо следует подчеркнуть, что нет общих подходов для оценки концентрации напряжений в зоне вмятины и не разработаны регулирующие документы для конструирования емкостей, учитывающие напряженно-деформируемое состояние в области вмятины. В статье представлены результаты конечноэлементоного анализа напряженно-деформируемого состояния цилиндрических баков со сферическими вмятинами. С помощью конечноэлементного анализа получены приближенные формулы для оценки коэффициентов концентрации напряжений, которые могут использоваться для расчета различных емкостей с различными вмятинами. Предполагается, что в области вмятины нет остаточных напряжений. Из расчета напряженно-дефорируемого состояния сделан вывод, что наибольшие напряжения наблюдаются, если вмятина располагается в нижней части емкости. Это обусловлено тем, что в нижней части емкости больше величина внутреннего статического давления. Предложен приближенный подход для расчета коэффицентов концентрации напряжений. Получены приближенные формулы для оценки коэффициента концентрации напряжений. Розглядаються результати скінченно-елементного аналізу напружено-деформованого стану циліндричного резервуару зі сферичними вм’ятинами. Отримано наближені залежності для коефіцієнтів концентрації напружень, які можуть бути використані при розрахунках циліндричних резервуарів зі сферичними вм’ятинами. Детально аналізується напружено-деформований стан резервуарів зі сферичними вм’ятинами